The Infact of the Project Based Learning (PjBL) Model on Strengthening the Pancasila Profile of Creative Thinking of High School Students - Miharja, Jajang; Baldah, Beti; Survani, Rifki (Journal Of Biology Education Research (JBER), 2024)
Education is an important factor in human life. Independent curriculum is present as a response to the tight competition for Human Resources, one of the goals of learning is to equip students with creative thinking skills. The PjBL model is a learning model that can bring out student creativity. This study aims to determine the effect of using project-based learning (PjBL) models on strengthening the Pancasila Profile in State Senior High School Students. This research method is a quasi-experimental with a pretest-posttest control group design. The research design used is Nonequivalent with a random sampling technique of 76 students selected as the experimental group and the control group. There were 7 test questions distributed, 20 student response questionnaires used, and 13 observation sheets used. Data analysis techniques are used to test the hypothesis. In testing this hypothesis, the technique used is the Sample T-test technique. The results of the study indicate that the use of the PjBL model can improve students' creative thinking skills. There is a difference in gain values ​​between the experimental and control classes. The gain value of the experimental class is higher than the gain value of the control class, so this study can conclude that the PjBL model has a significant effect on students' creative thinking skills. This study emphasizes the focus of PjBL and other meaningful tasks, namely by providing opportunities for students to work independently in constructing knowledge to create products as part of the realization of the Pancasila profile competency.